2022
DOI: 10.1111/and.14437
|View full text |Cite
|
Sign up to set email alerts
|

Coding and regulatory transcriptome comparisons between fertile and infertile spermatozoa identify RNA signatures of male infertility

Abstract: The aim of the present study was to identify RNA‐based signatures of male infertility by sperm transcriptome analysis. In this study, deep sequencing analyses of coding (mRNA) and regulatory (miRNA) transcriptomes were performed by pooling 15 oligo/oligoasthenozoospermic infertile sperm and 9 normozoospermic fertile sperm samples. Furthermore, interesting candidates were selected for validation by real‐time PCR. The comparison of miRNAs between cases and controls identified 94 differentially expressed miRNAs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…High cost of analysis, critical role of RNA preparation quality and relatively narrow range of variation in their expression are some of the limitations of using miRNAs as biomarkers of infertility. It is noteworthy that all studies on sperm miRNA in infertility, except our study [31], were microarray or RT-PCR based, next generation sequencing based studies would identify as yet unidentified miRNAs in sperm.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…High cost of analysis, critical role of RNA preparation quality and relatively narrow range of variation in their expression are some of the limitations of using miRNAs as biomarkers of infertility. It is noteworthy that all studies on sperm miRNA in infertility, except our study [31], were microarray or RT-PCR based, next generation sequencing based studies would identify as yet unidentified miRNAs in sperm.…”
Section: Discussionmentioning
confidence: 92%
“…On comparison of miRNA differential expression data across all published studies, including our case-control sequencing data [31], we found 497 differentially expressed miRNAs (DE-miRNAs) in sperm/semen of infertile patients as compared to fertile controls. Consistent differential expression of seven miRNAs across diverse studies indicated their strong association with infertility, suggesting their potential as markers of sperm fertility/quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of sample size has always been an objective problem in related research of human gametes. For example, some sperm proteomics studies can only detect single-digit samples [76,77], and sperm transcriptome analysis also has objective limitations.…”
Section: Limitation Of the Studymentioning
confidence: 99%
“…These studies showed a direct link between the messenger RNAs (mRNAs) and different classes of non-coding RNAs such as microRNAs (miRNAs) in men undergoing infertility treatment. As for the more holistic approaches, a total of 60,505 transcripts have been identified for the sperm transcriptome including 11,688 differentially expressed transcripts in infertile and fertile men (2022) [ 6 ]. A total of 6871 proteins have been identified for the sperm proteome, as reviewed by [ 7 ].…”
Section: Introductionmentioning
confidence: 99%